Audiovisual Media Communications in Adult Education: The case of Cyprus and Greece of Adults as Adult Learners - Constantinos Nicolaou; George Kalliris (European Journal of Investigation in Health, Psychology and Education, 2020)
Nowadays, audiovisual media technologies and audiovisual content (audiovisual media communications) play an important role in our physical/psychological health, education, and lifelong learning, causing the redefinition of the teaching methodology. As presented in the literature, the use of audiovisual media communications presuppose a new way of approaching effective teaching, which requires the educators on all educational levels and disciplines to display with competence many advanced skills and abilities. The aim of this research is to provide data that will contribute to the effective teaching utilizing audiovisual media communications in adult education. This research is a secondary research from two researches, which are qualitative and based on a quantitative method of analyzing. The primary data were collected through experiment method from adults (18 years and older), in Cyprus and Greece. The results confirm the current debate of using audiovisual media technologies within the educational process in technology-enhanced learning in education, both from the literature, and from the findings and results of various researches. This research is part of a larger, ongoing research that explores the multidisciplinary field that incorporates media, audiovisual content, and education (MACE), information and communications technologies (ICTs) in adult education (in Greece and Cyprus).